2021
DOI: 10.1097/anc.0000000000000962
|View full text |Cite
|
Sign up to set email alerts
|

From Expressing Human Milk to Breastfeeding—An Essential Element in the Journey to Motherhood of Mothers of Prematurely Born Infants

Abstract: BACKGROUND AND SIGNIFICANCELactation often plays a dominant role in how motherhood is experienced during the early postnatal period. 1 However, for mothers of premature infants (about 10% of infants worldwide), lactation and breastfeeding can be extremely challenging. 2,3 Premature infants are fragile due to their early birth (less than 37 weeks of gestational age), and they often require treatment and care at a neonatal intensive care unit (NICU). 4 A review from 2015 revealed that stable premature infants ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…During the interviews we discovered that the mothers of preterm infants had a strong desire to breastfeed. EBF of preterm infants during the hospital stay is key to successful breastfeeding after hospital discharge [ 33 ]. The facility should prepare parents of perterm infants for continued breastfeeding and ensure access to support services/groups after hospital discharge [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the interviews we discovered that the mothers of preterm infants had a strong desire to breastfeed. EBF of preterm infants during the hospital stay is key to successful breastfeeding after hospital discharge [ 33 ]. The facility should prepare parents of perterm infants for continued breastfeeding and ensure access to support services/groups after hospital discharge [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has reported that mothers experience many challenges to BF their preterm infants after discharge. There is evidence of a steady decline in mothers who continue to breastfeed their preterm infants following discharge from the hospital [ 13 , 19 , 20 ]. Therefore, it is important that mothers feel that they can provide safe care to the preterm infant after discharge at home.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only a small portion of mothers of preterm infants use EBF [ 18 ]. Research further reports that mothers with limited BF during NICU admission experience many challenges to BF their preterm infant after discharge [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusive nutrition with MOM has increased in NICUs with dedicated spaces and breastfeeding support staff [ 48 , 111 ].…”
Section: Determinants and Predictors Of Vlbws’ Nutrition With Materna...mentioning
confidence: 99%